Exosome tropism and various pathways in lung cancer metastasis - Chen, Hui; Liu, Lin; Xing, Gang; Zhang, Dan; A., Niumuqie; Huang, Jianlin; Li, Yaling; Zhao, Ge; Liu, Minghua (Frontiers in Immunology, 2025)
Lung cancer, characterized by its high morbidity and mortality rates, has the capability to metastasize to various organs, thereby amplifying its detrimental impact and fatality. The metastasis of lung cancer is a complex biological phenomenon involving numerous physiological transformations. Exosomes, small membranous vesicles enriched with biologically active components, are pivotal in mediating intercellular communication and regulating physiological functions due to their specificity and stability. Extensive research has elucidated the production and functions of exosomes in cancer contexts. Multitude of evidence demonstrates a strong association between lung cancer metastasis and exosomes. Additionally, the concept of the pre-metastatic niche is crucial in the metastatic process facilitated by exosomes. This review emphasizes the role of exosomes in mediating lung cancer metastasis and their impact on the disease’s development and the progression to other tissues. Furthermore, it explores the potential of exosomes as biomarkers for lung cancer metastasis, offering significant insights for future clinical advancements.